PREPARATION OF FUTURE TEACHERS OF FOREIGN LITERATURE FOR THE FORMATION OF STUDENTS OF SUBJECT COMPETENCIES - Rozman, Iryna (Mountain School of Ukrainian Carpaty, 2021)
Extremely popular and important was the expression that we get knowledge for life. Modern conditions of sociopolitical life have changed the wording “education for life” to “education as long as life”. It is not enough to get a "baggage of knowledge" and be content with it. The pace of development of our life is so rapid that it is necessary to constantly engage in self-development, study foreign languages, information technologies, use the experience and advice of works of art in a new perspective: rethinking the need to develop competencies that we did not think about when reading literary works at school or higher educational institution. Now we are paying attention to the knowledge component, the active component and the value component. We read the work, identified the topic, idea, system of images, used comparative characteristics, chronological tables. Then logical schemes began to appear-notes, comparative analysis, audiobooks, presentations. Life shows that the requirements of the modern system and new approaches to the development of education are due to the fact that in a modern integrated community, both schoolchildren and students can no longer study in isolation, limiting themselves to a traditional rather closed society: teachers, friends, family. Telecommunications open windows to the wider world. Students get access to the richest information resources of networks, the opportunity to choose the necessary material in addition to what is available in the textbook. The task of the teacher is to form key competencies over the years of training-to teach students to select the necessary information, evaluate their quality, show selectivity in their consumption, form the ability to find the required data. As a rule, in the process of learning, students form, first of all, empirical thinking, concepts are presented in a ready-tomemorize form, the process of their formation is not conscious, students do not master a method of action that would allow them to independently apply knowledge in practice. The purpose of the article is to consider the communicative aspect of the formation of oral speech development skills, the ability to analyze the artistic component of literature, the active component and the value component of learning. In order to train future teachers of foreign literature in subject competencies, first of all it is necessary to get well acquainted with the Program on Foreign literature, focus on the gradual development of all components. It is necessary to understand the principle of drawing up a Program on foreign literature for grades 10-11. In grades 10-11, a new stage of literary education begins – creative and critical reading, which will be a logical continuation of the previous stages.